Type 2 diabetes mellitus prediction model based on ensemble boosting method with Principal Component Analysis - Sornam, M; Meharunnisa, M (International Journal of Computer Sciences and Engineering, 2025)
In the recent years, data mining has been employed in the medical field for extracting and manipulating information, and aids within the higher process. There is a growing want for the medical establishments to be extra suggested and knowledgeable concerning the diseases and to understand the risk factors before diagnosis. Predicting the results of a process with a high level of accuracy is a difficult task. In this study we took the advantage of the data mining models to predict the Type – 2 Diabetes mellitus. The benchmark dataset, “Pima Indian Diabetes” dataset is used for this study. The main objective of this study is to propose the extensive data pre-processing such as imputation of missing values and a feature engineering technique namely ‘Principal Component Analysis’ are used to transform the dataset into a compressed form. Ensemble or classifier combination method called boosting method such as Gradient boosting machine and Random Forest are used. The most downside that’s attempting to be resolved isn’t solely to extend the accuracy however additionally to retain all the information in the data set while not removing the missing data. The missing data are imputed by a method called ‘predictive mean matching’. The results show that the ensemble learners, once used alongside PCA attained 100% accuracy of prediction. Moreover, it ensures that no missing information must be removed and might be imputed to confirm the data quality is enough. As a result, the model is shown to be helpful for the real time prediction of Diabetes Mellitus.